The Habitualization of Religious Values in Character Education at the Ulin Nuha Al Islami Bogor Foundation - Marwah, Nabilah; Sukendar, Egi Agustian Rahmat (PT ARRUS Intelektual Indonesia, 2023)
Educational institutions are important instruments in shaping the character of students with religious values that refer to understanding Islamic religious values and the habit of worship, both in the form of mahdhoh worship and ghair mahdhoh worship. This study aims to photograph and find out the process of internalizing religious values through providing an understanding of religious knowledge and habituation of worship as a means of character building for students at MTS Ulin Nuha Al Islami Bogor. This study uses a qualitative approach with a type of phenomenology. The subjects of this study included stakeholders and religious teachers and representatives of students from class VII to IX. And researchers used three data collection techniques, namely interviews, observation and documentation. Then this study uses the data analysis model of Miles, Huberman, and Saldana in which there are three stages including data condensation, data presentation, conclusion/verification. The results of this study are that the provision of religious knowledge and the habit of worship as a form of instilling character in MTS Ulin Nuha Al Islami Bogor students has been successful. Judging from Thomas Lickona's theory of character education which consists of moral knowledge, moral feelings and moral behavior. The subjects are Mulok Tahfizh, Hadith, Prayers and the Classic Book or Adab. Habit of worship routines such as praying dhuha together, praying dhuhur in congregation, memorizing juz ama. As well as getting used to cover the genitals. Instilling leadership values, tolerance and love of knowledge.